Bologna centrale high-speed train station. Visual-sound syncretisms for a functional space - Ciarpella, Annalisa; Moscatelli, Giulia; Quagliotto, Arianna; Vitale, Giovanni (E|C, 2020)
In the design of a space, what is the value of sound? Can it be functional for the orientation and use of space by the subjects? These are the questions at the base of our analysis of the Bologna AV Railway Station. The AV Station has been designed as a path, as a proposal of structured movement for subjects: rather than simply space, it is therefore a place of spatial practices. The isotopy of movement is articulated along all the Station’s levels of meaning, from space design to sound dimension and subject practices. It has been observed how the visual and sound dimensions work in syncretism in order to create scenarios of action; and the sound concurs to determine sometimes precise, sometimes unexpected and erroneous reconfigurations of the space meaning for the subjects. Sound is a concrete element of the space designing and enunciation strategy, from which depend functional syncretisms, dyscrasias and resemantizations. The analysis focuses on the relational nature of the elements that make up the space and on the effects of meaning produced by syncretism between visual and sound dimensions, in order to gather new and profound meanings: in a perspective that is extended to the soundscape, the sound phenomena determines the major effects of meaning, thus influencing the modes of fruition of the space by the subjects that go through it.